Women in Politics of Tin Resources: Multiple Problems of Human Rights under the Curse Shadows of Natural Resources - Tin Mining in Bangka Belitung Islands - Rendy Rendy (Proceedings of AICS - Social Sciences, 2017)
The economic practice of tin mining in Bangka-Belitung (Babel) Islands Province surely is not separated from direct or indirect of women involvement. The demography of mining society in Babel precisely displays of women are massively in mining arena. The rule of law and practice of mining tends to uncontrollable, liar, destructive and exploitative so far has shown surely the negative impacts which overburden the women position. On the other hand, they should be smarter in managing of domestic needs, nurturing their children; meanwhile, the others have to go down to the river, to ‘camui-camui’ (holes) as an ex of tin mining areas until evening. Moreover, they face several of complexities whether internal nor external threats; like domestic violence, divorce, gambling, HIV AIDS, a dangerous accident of mining, and etc. These reflect how dangerous, weak, and heavy of multiple burdens. Those are also relevant to the disease of tin mining which always shows some evidence; gambling, prostitution, alcohol, narcotics. However; women dominantly suffer social burden among capitalism war where tin has become an important material to support their industries. This article aims at exploring how far a critical feminist human right perspective could influence to bear on women's human right circumstance and complex burden faced in Babel. This project analyzed women’s presence and also its burden in tin mining issues whether in private or public sphere. I addressed emerging issues and questions about the status of human rights in tin mining issues.